Planning and clinical strategy in direct composite restorations - Jordão-Basso, Keren Cristina Fagundes [UNESP]; Pedro, Fábio Luiz Miranda; Barros, Yolanda Benedita Abadia Martins de; Silva, Monica Barros da; Tavares, Rudys Rodolfo de Jesus; Andrade, Marcelo Ferrarezi de [UNESP]; Segalla, José Claudio Martins [UNESP] (Incessant Nature Science Publishers, 2014)
Patients are seeking increasingly the expertise of dental surgeons for esthetic dental improvement. The dental surgeons should know the restorative materials and techniques in order to optimize the clinical practice and to obtain satisfactory results. Also the dentist should know the average heights and widths of the anterior teeth to detect the esthetic disharmony and to eliminate it for reproducing the correct dental anatomy. Thus, this study aimed to describe a clinical case report of direct restoration using the palatal barrier technique.